Mind the gaps: What's missing in political economy analysis and why it matters - Hudson, David; Marquette, Heather (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for t he OECD-DAC Network on Governance (GovNet). It brings together a colle ction of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, witho ut attempting to offer definitive guidance – instead aiming to stimula te thinking and debate. To aid this process the book is centred on a f ictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the e volution of donor thinking, and highlights future challenges in the ag e of the Sustainable Development Goals. Each section introduces both t echnical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT